2001
DOI: 10.1128/mcb.21.19.6626-6639.2001
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Wnt Signaling and Activation of Multiple Metabolic Pathways in Response to Thyroid Hormone-Stimulated Cell Proliferation

Abstract: To investigate the transcriptional program underlying thyroid hormone (T3)-induced cell proliferation, cDNA microarrays were used to survey the temporal expression profiles of 4,400 genes. Of 358 responsive genes identified, 88% had not previously been reported to be transcriptionally or functionally modulated by T3. Partitioning the genes into functional classes revealed the activation of multiple pathways, including glucose metabolism, biosynthesis, transcriptional regulation, protein degradation, and detoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 60 publications
7
63
0
Order By: Relevance
“…This would simultaneously lower Tcf activity and augment AR transactivation. Such a model is also considerate of other reports of nuclear receptor repression of Tcf, including the RAR (Easwaran et al, 1999) and the thyroid receptor (Miller et al, 2001), two hormone receptors that are expressed constitutively in the nucleus.…”
Section: Other Nuclear Receptors and Tcf/lef Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…This would simultaneously lower Tcf activity and augment AR transactivation. Such a model is also considerate of other reports of nuclear receptor repression of Tcf, including the RAR (Easwaran et al, 1999) and the thyroid receptor (Miller et al, 2001), two hormone receptors that are expressed constitutively in the nucleus.…”
Section: Other Nuclear Receptors and Tcf/lef Signalingmentioning
confidence: 99%
“…For example, it has been shown that bcatenin increases the activity of the retinoic acid receptor (RAR) on RAR-responsive promoters with a reciprocating downregulation of the b-catenin/Tcf signaling pathway by the RAR (Easwaran et al, 1999). Other reports have shown Wnt signaling to be functional in human thyroid cells (Helmbrecht et al, 2001) with triiodothyronine (T 3 ) also having the capacity to silence the b-catenin/Tcf pathway (Miller et al, 2001). With the structural conservation between members of the steroid nuclear receptor family, it is reasonable to hypothesize that similar interactions with the Wnt pathway may exist with other nuclear steroid receptor members.…”
Section: Introductionmentioning
confidence: 99%
“…Selection of clones for arraying is described elsewhere (Miller et al, 2001). The complete set of clones in the TIGR Rat Gene Index can be queried at 5http://www.tigr.org/tdb/rgi/index.html4.…”
Section: Amplification Of Cdna Clones From the Tigr Rat Gene Indexmentioning
confidence: 99%
“…Wnt signaling inactivates the b-catenin destruction complex, so that b-catenin is stabilized, accumulates in the cytoplasm and nucleus, and forms heterodimers with the DNA-binding factors belonging to the LEF/ TCF family (reviewed in Huelsken and Behrens, 2002). As a result, significant changes occur in the gene expression program (reviewed in Hecht and Kemler, 2000;Miller et al, 2001). In addition, Wnt signaling can be antagonized extracellularly by secreted factors such as Wnt inhibitory factor-1 (WIF-1), Cerberus, members of the Dickkopf (DKK) family, and soluble Frizzled-related proteins (sFRP) (Kawano and Kypta, 2003).…”
Section: Introductionmentioning
confidence: 99%